A case of 10 year follow-up after transcatheter closure of a traumatic ventricular septal defect. (24th May 2016) - Chi, Di; Sun, Yong; Tan, Miaoxin; Zheng, Yang; Liu, Xianglan; Yu, Bo; Wu, Jian
Abstract: Ventricular septal defect (VSD) is an uncommon complication of penetrating heart injuries, but transcatheter closure has emerged as a new technique and is widely used worldwide. In spite of high success rate and minimal operative mortality, short-term follow-up post-operation and long-term follow-up post-operation have not been observed. In the present study, we report a case of cardiac injury after stabbing himself with a dagger. The patient was diagnosed with a post-traumatic VSD with left-to-right shunt and was transferred to theatre where the defect was successfully repaired. Seven days later, on echocardiography examination, an occluder closing the defect with no residual leak was revealed. During the extensive follow-up over 10 years, no complication of occluder break, translocation and thrombosis formation occurred.